The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.jp.7211465
|View full text |Cite
|
Sign up to set email alerts
|

Patent ductus arteriosus: pathophysiology and management

Abstract: Patent ductus arteriosus (PDA) in preterm newborns prior to 28 weeks of gestation has led to many challenges regarding the type and timing of treatment regimens. A PDA results in increased pulmonary blood flow and redistribution of flow to other organs. Several co-morbidities (i.e., necrotizing enterocolitis, intracranial hemorrhage, pulmonary edema/ hemorrhage, bronchopulmonary dysplasia, and retinopathy) are associated with the presence of a PDA, but whether or not a PDA is responsible for their development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
164
2
24

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(194 citation statements)
references
References 11 publications
2
164
2
24
Order By: Relevance
“…Hemorrhagic complications among ELBW neonates can be significant and therefore medications that do not impair platelet function might be considered preferentially above alternative medications that do. 17,20 In this study we assessed platelet plug formation of 20 NICU patients where ibuprofen dosing had been ordered by the clinician in order to close a PDA. We assessed platelet plug formation using two tests: the template bleeding time and the PFA-100 closure time.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic complications among ELBW neonates can be significant and therefore medications that do not impair platelet function might be considered preferentially above alternative medications that do. 17,20 In this study we assessed platelet plug formation of 20 NICU patients where ibuprofen dosing had been ordered by the clinician in order to close a PDA. We assessed platelet plug formation using two tests: the template bleeding time and the PFA-100 closure time.…”
Section: Discussionmentioning
confidence: 99%
“…1 A hemodynamically significant sPDA is associated with serious co-morbidities such as congestive heart failure, pulmonary hemorrhage, necrotizing enterocolitis, bronchopulmonary dysplasia and retinopathy of prematurity. 1,2 Although spontaneous closure of the ductus arteriosus can occur, the majority of ELBW infants with sPDA require pharmacological treatment or surgical ligation.…”
Section: Introductionmentioning
confidence: 99%
“…2 The authors mention that fluid intake did not predict the development of bronchopulmonary dysplasia when controlling for other known risk factors. Did any infants in the study develop pulmonary hemorrhage?…”
mentioning
confidence: 99%
“…The incidence of a symptomatic PDA among extremely low birth weight (ELBW) infants is reported to be 55 to 70%. 2 A large multicenter randomized control trial (TIPP trial) of infants <1000 g birth weight showed that indomethacin prophylaxis reduced the incidence of symptomatic PDA from 50% (placebo) to 24%. 3 The low PDA incidence in the study by Stephens et al 1 may have been secondary to indomethacin prophylaxis and/or because they only included infants that survived to discharge, which might limit the ability to generalize their findings to initial fluid management.…”
mentioning
confidence: 99%
See 1 more Smart Citation